Perbandingan Simulated Annealing dan Particle Swarm Optimization untuk Mencari Waktu Optimal Pada Optical Ring Resonator - Ahmad Rauhan; Teuku Harun Alrasyid; Herminarto Nugroho (JURNAL TEKNOLOGIA, 2020)
Optical Beamforming Network (OBFN) is a device to receive signal and send them again to the addressed receiver or another device. For the incoming signal to be received by OBFN then the signal of the receiver needs to be at the same phase with the signal of the sender, therefore it is required to have a device to control the phase of the received signal. Optical Ring Resonator (ORR) is a device used for giving a delay to the signal so that the phase received have equal phase with the sended signal. To determine the value of the optimal delay time of the ORR, we use two kinds of optimization method and there are simulated annealing and particle swarm optimization. These two kinds of optimization method used because the values that they produce more optimal than the rest of the other method. When using simulated annealing method, the value that produced use more iteration than when using praticle swarm optimization method. The optimal delay value of the ORR is very important for the OBFN to be able to sum the incoming signal so that the power of the signal did not subtract each other. If signals comes to the OBFN in a large scale, the ORRs that used is installed in cascade setting.